LEGAL AND PSYCHOLOGICAL ASPECTS OF PROFESSIONAL ACTIVITY HEAD OF THE SECURITY POLICE - Ostapovych, Volodymyr (PSYCHOLOGICAL JOURNAL, 2020)
The article is devoted to the issue of defining and generalizing the legal and psychological aspects of the professional activity of heads of territorial police units in the context of the exercise of their powers in the administrative sphere. It is stated that the head of the territorial unit of the security police should know at a high level the legislative and normative documents regulating the activity of the security police, as well as interaction with the state authorities and local self-government bodies; departmental and international normative documents regulating the observance of human rights; organizational structure and peculiarities of activity of units of the National Police of Ukraine, types and forms of reporting, basic legal provisions for the storage of information with restricted access, registration of relevant official documents, etc. In addition, police officer should have information about the operational situation and the places of the most likely crime. The profession of the head of the territorial unit of the security police places certain requirements on the level of psychomotor properties of the psyche and the sensory-perceptual sphere. It should have a sufficient level of functional brain activity, a developed vestibular apparatus, and a sufficiently high rate of simple reaction and reaction to a moving object. Police officer also needs to have advanced cognitive processes (attention, memory, thinking), and speech functions. The profession of the head of the territorial security police force sets certain requirements for the general and special professional abilities of employees (high and medium level of verbal intelligence, higher than average speed of divergent thinking, formed mental operations of analysis and synthesis, induction and deduction, abstraction). The Police leader must be able to persuade, influence the interlocutor, be responsible for their actions and orders, give an objective assessment of their own actions and actions of others, optimally combine business and personal contacts, attract attention and interest of people, and arouse their feelings of trust. Organizational and managerial capabilities are also significant for the professional activity of the head of the territorial police unit. The results of the empirical study revealed a list of necessary competencies that the head of the territorial police unit must possess: strong or medium-strong type of nervous system, high or average level of general abilities, a high level of development of special professional abilities, high or average level of communicative abilities, high psychotic skills properties, character traits and emotional-volitional qualities, a sufficient level of development of cognitive processes.